Clinical Outcomes and Quality of Life in Recipients of Livers Donated after Cardiac Death - Neehar D. Parikh; Anton I. Skaro; Daniela P. Ladner; Vadim Lyuksemburg; Joshua G. Cahan; Amna Daud; Zeeshan Butt (Gastroenterology Research and Practice)
Donation after cardiac death (DCD) has expanded in the last decade in the US; however, DCD liver utilization has flattened in recent years due to poor outcomes. We examined clinical and quality of life (QOL) outcomes of DCD recipients by conducting a retrospective and cross-sectional review of patients from 2003 to 2010. We compared clinical outcomes of DCD recipients (n=60) to those of donation after brain death (DBD) liver recipients (n=669) during the same time period. DCD recipients had significantly lower rates of 5-year graft survival (P<0.001) and a trend toward lower rates of 5-year patient survival (P=0.064) when compared to the DBD cohort. In order to examine QOL outcomes in our cohorts, we administered the Short Form Liver Disease Quality of Life questionnaire to 30 DCD and 60 DBD recipients. The DCD recipients reported lower generic and liver-specific QOL. We further stratified the DCD cohort by the presence of ischemic cholangiopathy (IC). Patients with IC reported lower QOL when compared to DBD recipients and those DCD recipients without IC (P<0.05). While the results are consistent with clinical experience, this is the first report of QOL in DCD recipients using standardized measures. These data can be used to guide future comparative effectiveness studies.